Activity of Soil Microorganisms During the Growth of Sweet Corn (Zea Mays Saccharata Sturt) in the Second Planting Time with the Application of Fertilizers and Biochar - . Dermiyati; Agus Karyanto; Ainin Niswati; Jamalam Lumban Raja; Sugeng Triyono; Nyang Vania Ayuningtyas Harini (JOURNAL OF TROPICAL SOILS, 2017)
Efforts to increase the production of sweet corn can be done with the application of fertilizers, either inorganic, organic orits combination. In addition, the application of soil amendments such as biochar is also expected to improve soil fertility that will indirectly increase the production of sweet corn.Organonitrophos fertilizer is an organic fertilizer developed by lecturers of Faculty of Agriculture, University of Lampung. The research was aimed to study effect the combination of organonitrophos, and inorganic fertilizers, biochar and the interaction between fertilizer combination and biochar on soil respiration and soil microbial biomass.The research was conducted in the Integrated Field Laboratory of Lampung University using 6x2 factorial in a Randomized Block Design with 3 replications. The first factor was six levels combination of organonitrophos and inorganic fertilizers (P0, P1, P2, P3, P4, and P5). The second factor was two levels of biochar dosage (B0 and B1). Data was analyzed by Analysis of Variance and followed by the Least Significant Difference (LSD)Test at 5% level. The observed variables were soil microorganism activity likely soil respiration and soil microbial biomass. The results showed that P3B1treatment (300 kg Urea ha-1, 125 kg SP-36 ha-1, 100 kg KCl ha-1 + 2500 kg organoitrophos ha-1) was the highest soil respiration at of 60 days after planting (DAP). P5 treatment (5000 kg Organonitrophos ha-1) has the highest soil microbial biomasscompared to other treatments at 60 and 90 DAP. B1 treatment (5000 kg biochar ha-1) has higher soil respiration and soil microbial biomasscompared to treatment (0 kg biochar ha-1. There was an interaction between combination of organonitrophos and inorganic fertilizers and biochar on soil respiration at 90 DAP. However, there was no interaction between fertilizer combination and biochar on soil microbial biomass.Keywords: Biochar, Fertilizer Combination, Organonitrophos, Soil Microbial Biomass Carbon and Soil Respiration